Pengembangan LKPD Berintegrasi Nilai-Nilai Keislaman untuk Melatih Kemampuan Pemecahan Masalah Matematis - Tri Nanda Akbar Maualana; Tasnim Rahmat; M. Imamuddin; Pipit Firmanti (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This research was motivated by the problems found, namely the lack of learning media, the LKPD used had not trained mathematical problem solving abilities, the existing LKPD was LKPD created by educators who had not been connected to Islamic teachings, resulting in a decline in students' mathematical problem solving abilities. This research aims to produce LKPD integrating Islamic values to train problem solving skills in class This research is development research or RnD using the Sugiyono development method. The instruments used were validation sheets, student response questionnaires, and mathematical problem solving ability tests. The data analysis techniques used are validity data analysis, practicality analysis, and effectiveness analysis. Based on the development research that has been carried out, an LKPD with a validity level of 80% is in the valid qualification, for the practicality qualification, namely 78.41% is in the practical criteria, and for the effectiveness level, namely 80,76% is in the effective qualification. It can be concluded that the LKPD integrates Islamic values to train mathematical problem solving abilities which was developed including valid, practical and effective criteria.